(untitled) (The Research of Medical Science Review, 2025)
Background: Vaccination programs are critical in preventing disease outbreaks, particularly in low- and middle-income countries with limited healthcare infrastructure. Evaluating the effectiveness of these programs helps assess their impact on public health, guiding future interventions and resource allocation. Methodology: - This systematic review assesses the effectiveness of vaccination programs in low- and middle-income countries (LMICs), focusing on coverage, disease reduction, and barriers to uptake. A total of 25 published original articles between the years 2010 and 2024 were finally chosen on the vaccination program. Studies included in the work encompassed different types of designs primarily RCTs, cohort studies, and case-control studies. The studies were retrieved from scholarly databases such as PUBMED, Medline, WHO Global Research on COVID-19, and Google Scholar using key terms; vaccination programs and vaccination-preventable diseases. Several factors including vaccine hesitancy and access to vaccines are highlighted as major challenges impeding progress towards the implementation of the Global Immunization Agenda 2030 goals. Results: - The use of vaccines in disease prevention is a key intervention essential for disease control interacting positively with health status in LMIC countries. Research has proved that vaccines greatly minimize diseases such as rotavirus, measles, influenza as well as dengue. Mobile conditional cash transfers, for instance, have been effective in the case of immunization while there has been protection for mothers as well as their children through maternal vaccination. Vaccination also adds credence to health systems as it relieves health services. Efforts such as HPV vaccination have boosted health equity whereas, economic assessment has reflected the cost effectivity. Disease eradication provides Long-term benefits, as seen with polio, measles, and rotavirus vaccines, enhancing global health security. Conclusion: - Routine immunization and expanded program of immunization guarantee control of communicable diseases, and enhance health systems and life courses in low and middle-income countries; logistical barriers and vaccine hesitancy are some of the barriers that may limit the success of the program; however, there are some proven solutions like mobile health solutions and the act of providing incentives like cash to those who accept to be vaccinated.